Application of Collaborative for Academic, Social, and Emotional Learning-Based Game-Based Learning Model in Improving Mathematics Learning Outcomes in Class IV A - Sulistyowati, Prihatin; Rosdiana, Devi Retno; Suswati, Hermin (Actual Insight, 2025)
This study aims to analyze the effectiveness of the application of the Game-Based Learning (GBL) model based on Collaborative for Academic, Social, and Emotional Learning (CASEL) in improving the mathematics learning outcomes of grade IV A students of Bandungrejosari 3 Public Elementary School Malang. The research background is the low learning outcomes and student engagement in mathematics learning, along with the limited integration of social-emotional learning components in classroom practices. The method used is Classroom Action Research which is carried out in three stages, namely pre-cycle, cycle I, and cycle II, following the Kemmis and McTaggart model that includes planning, implementation, observation, and reflection. Data were collected through learning outcome tests and student response questionnaires administered at each stage. The results showed a significant increase in the completeness of learning outcomes from the pre-cycle stage to cycle II, indicating that students’ academic performance in mathematics improved through the implementation of this model. In addition to academic achievement, the application of the CASEL-based Game-Based Learning model also contributed to the development of students’ social-emotional aspects, particularly in collaboration, communication, empathy, and self-regulation skills, which were observed during group activities and interactive game sessions. These findings indicate that integrating CASEL-based GBL is effective in promoting both cognitive and social-emotional competencies in elementary school students.